The Quality of Internal Audit Implementation is Affected By The Competence And Objectivity of Internal Auditor at PT Sarana Panca Nusantara - Muhammad Mulia Ramadhan (Universitas Indonesia Membangun, 2025)
The Competence and Objectivity of Internal Auditors play a critical role in supporting the advancement and effectiveness of an organization. Auditor competence enables the execution of audit activities in a more effective and efficient manner, thereby contributing positively to the organization’s overall performance. This study aims to examine the extent to which Competence influences the Quality of Internal Audit Implementation, to assess the impact of Objectivity on audit to assess how objectivity affects audit quality, and to evaluate the combined effect of Competence and Objectivity on the overall Quality of Internal Audit Implementation. The research method used is quantitative descriptive with data collection techniques through the distribution of questionnaires with a sample size of 41 people. Data analysis was carried out using multiple regression tests, determination coefficient tests and hypothesis tests. The findings of the study indicate that Auditor Competence has a significant effect on the Quality of Internal Audit Implementation. Similarly, internal auditor objectivity also exerts a significant influence on audit quality. Furthermore, both Competence and Objectivity collectively contribute to the effectiveness and Quality of Internal Audit Implementation. The implications of the research for those being audited use common and easy-to-understand language so as not to cause misinterpretation.